RT-PCR APPLICATION FOR DETECTION OF THE STRAWBERRY CRINKLE VIRUS AND STRAWBERRY MILD YELLOW EDGE VIRUS DISEASES ON STRAWBERRY PLANTS (FRAGARIA VESCA L.) CULTURED IN VITRO - Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2011)
The reverse transcriptase-polymerase chain reaction (RT-PCR) was applied for detection of the strawberry crinkle vims (SCV) and strawberry mild yellow edge vims (SMYEV) diseases on three strawberry cultivars: "My Da", "My Huong" and "Phap". The in vitro leaves of these three strawberry cultivars were used for this research. Three different culture media were used. Calli were induced on the MS medium containing 1 mg/l TDZ, 0.1 mg/l 2,4-D, 30 g/l sucrose and 8 g/l agar (1); shoots were regenerated on MS medium containing 0.2 mg/l BA, 30 g/l sucrose and 8 g/l agar (2); roots were formed on MS medium containing 5 ml/1 B5 vitamin, 30 g/l sucrose and 8 g/l agar (3). The RNA extraction from leaf tissues according to the method of Mazzara and James (2000) and then, the extracted RNA transposition into RT-PCR using the StrataScript® One-Tube RTPCR Kit of ITS Vietnam. In this research, two primer pairs SCIDFW-SCIDRV and SMlDFW-SMlDRV were used for the detection of these virases by RT-PCR. The amplified products had expected sizes: 345 bp and 271 bp, respectively. We found that the RT-PCR test with these two primer pairs SCIDFW-SCIDRV and SMlDFW-SMlDRV was capable to detect the SCV and SMYEV diseases on in vitro strawberry plantlets. The infection rates of SCV and SMYEV on three strawberry cutivars were "My Da": 2.66% SCV and 3.3% SMYEV; "My Huong": 4% SCV and 2.66% SMYEV; "Phap": 4.6% SCV and 1.3% SMYEV. Vims-free strawberry plantlets were obtained, and were used as a vims-free expiant source for the strawberry propagation.